Serum paraoxonase 1 activity and protein N-homocysteinylation in primary human endometrial cancer - Krzysztof Gałczyński; Jerzy Bełtowski; Łukasz Nowakowski; Danuta Vasilevska; Tomasz Rechberger; Andrzej Semczuk (Tumor Biology, 2018)
Paraoxonase 1 plays an important role in protection from oxidative stress and also decomposes homocysteine thiolactone, the toxic metabolite of homocysteine. A limited number of reports evaluated the role of paraoxonase 1 in women affected by female genital tract neoplasms, including endometrial cancer. This study aimed to analyze the paraoxonase activity in the group of endometrial cancer patients (n = 48) who underwent primary surgery and to compare the data available with a well-matched control group (n = 30). Due to the role of paraoxonase 1 in the metabolism of homocysteine (Hcy) thiolactone, the amount of Hcy-thiolactone as well as total serum Hcy concentrations was also measured. Serum paraoxonase 1 activity toward synthetic substrates, paraoxon and phenyl acetate, in the study group was significantly lower compared to the control one. The mean paraoxonase 1 activity toward homocysteine thiolactone tended to be lower in the endometrial cancer group but this difference was not significant. There was no relationship between endometrial cancer and Q192R polymorphism of PON1 assessed by the dual substrate method. No differences in paraoxonase 1 activity between endometrial cancer subgroups according to clinico-pathological features were detected. Total serum homocysteine and protein-bound homocysteine thiolactone did not differ between control and cancer groups. In conclusion, reduced paraoxonase 1 activity suggests diminished important antioxidant mechanisms during the development of primary endometrial cancers in humans. PON1 Q192R polymorphism is not associated with the risk of endometrial cancer. Despite lower paraoxonase 1 activity, homocysteine concentration, and protein N-homocysteinylation in endometrial cancers do not differ from matched controls.